2018
DOI: 10.1016/j.ejvs.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Versus Open Surgical Intervention in Patients with Takayasu's Arteritis: A Meta-analysis

Abstract: This meta-analysis has shown a lower risk of restenosis with open surgical intervention than with endovascular intervention. Stroke was generally more common with open surgical intervention than with endovascular intervention. However, there were differences according to the location of the lesion, and the risk of stroke in open surgery is higher when the supra-aortic branches are involved rather than the renal arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 47 publications
1
20
0
3
Order By: Relevance
“…In these patients, timely revascularization should be performed as prognosis for conservative management is poor [5,6]. Open surgical approach, including CABG, patch angioplasty or transaortic coronary ostial endarterectomy, is preferred as endovascular interventions have been associated with an increased risk of restenosis [7]. Although CABG is most commonly employed, currently there is no data to prove superiority of one procedure over the other.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, timely revascularization should be performed as prognosis for conservative management is poor [5,6]. Open surgical approach, including CABG, patch angioplasty or transaortic coronary ostial endarterectomy, is preferred as endovascular interventions have been associated with an increased risk of restenosis [7]. Although CABG is most commonly employed, currently there is no data to prove superiority of one procedure over the other.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis included 770 patients and 1363 lesions. Of these, 389 patients were treated endovascularly and 420 underwent surgical revascularisation [44]. Overall, the incidence of restenosis was lower following open surgery.…”
Section: Endovascular Versus Open Surgerymentioning
confidence: 99%
“…Outside the aorta, angioplasty is commonly employed for the treatment of stenoses in branch arteries. Although opinion remains divided on the use of stents, most studies have reported higher restenosis and recurrence rates when stents are deployed when compared to angioplasty alone [43,44,[49][50][51][52]. Increasingly, stents are reserved for the treatment of procedural complications such as dissection or for recurrent lesions.…”
Section: Endovascular Versus Open Surgerymentioning
confidence: 99%
“…Surgical intervention for TA includes two interventional options: 1) endovascular intervention, including percutaneous transluminal angioplasty and stent-graft placement and 2) open surgical intervention, including surgical bypass grafting, endarterectomy, and graft patch for short segment lesions [24]. intervention was higher when the supra-aortic branches were involved rather than the renal arteries [6].…”
Section: Takayasu's Arteritismentioning
confidence: 99%
“…Stroke can happen as a complication of vasculitis treatment. Some forms of surgical interventions for vasculitis treatment have been reported to result in stroke as a complication [6].…”
Section: Introductionmentioning
confidence: 99%